Mothers’ Experiences of French Mothertongue Maintenance: Re/Gaining Fluency in a Linguistic Minority - Isabeau Iqbal (Adult Education Research Conference, 2004)
This qualitative study explores how francophone mothers, who have taken on the primary responsibility for teaching French to their pre-school aged children, explain support and barriers to regaining and maintaining their own native language when they mother in a linguistic minority.